2015
DOI: 10.1177/0394632015613039
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of quercetin glycosides, rutin, and isoquercetrin against 6-hydroxydopamine (6-OHDA)-induced neurotoxicity in rat pheochromocytoma (PC-12) cells

Abstract: There is increasing evidence that free radicals induced oxidative stress is a major causative agent in the pathogenesis of neurodegenerative diseases, particularly Parkinson's disease. Quercetin glycosides, namely rutin and isoquercitrin, are flavonoid polyphenol compounds found ubiquitously in fruits and vegetables and have been known to possess antioxidant effects. This study was designed to compare the neuroprotective effects of quercetin glycosides rutin and isoquercitrin in 6-OHDA-induced rat pheochromocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 48 publications
1
39
0
Order By: Relevance
“…Imipramine [247] Isobavachalcone [248] Isochlorogenic acid [167] Isoquercetin (Isoquercitrin) [249] Kaempferol [128,160,193,194] Kaempferol, 3-O-a-l arabinofuranoside-7-O-a-l-rhamnopyranoside [214] KR33493 [250] Kukoamine [251] Lestaurtinib [164] Lipoic acid [252][253][254] Luteolin [128] LY354740 [115] M10 [24] M30 (VAR10303) [112,255] M99 [24] Macranthoin G [256] Magnesium lithospermate B [257] [160,193,194,267] [18F]MPPF [107] MSX-3 [268] Myricetin [128,269,270] Myricitrin [271] Naringenin [128,272] Naringin [117,273,274] Nicotinamide adenine dinucleotide phosphate (NADPH) [275,276] Nicotinamide mononucleotide [277] Nitecapone [278] Nordihydroguaiaretic [160,193,194] Oleuropein…”
Section: Compound Name(s) Referencesmentioning
confidence: 99%
“…Imipramine [247] Isobavachalcone [248] Isochlorogenic acid [167] Isoquercetin (Isoquercitrin) [249] Kaempferol [128,160,193,194] Kaempferol, 3-O-a-l arabinofuranoside-7-O-a-l-rhamnopyranoside [214] KR33493 [250] Kukoamine [251] Lestaurtinib [164] Lipoic acid [252][253][254] Luteolin [128] LY354740 [115] M10 [24] M30 (VAR10303) [112,255] M99 [24] Macranthoin G [256] Magnesium lithospermate B [257] [160,193,194,267] [18F]MPPF [107] MSX-3 [268] Myricetin [128,269,270] Myricitrin [271] Naringenin [128,272] Naringin [117,273,274] Nicotinamide adenine dinucleotide phosphate (NADPH) [275,276] Nicotinamide mononucleotide [277] Nitecapone [278] Nordihydroguaiaretic [160,193,194] Oleuropein…”
Section: Compound Name(s) Referencesmentioning
confidence: 99%
“…In addition, several studies demonstrated the neuroprotective effects exerted by some quercetin glycosides such as rutin, isoquercetin and hyperoside in in vitro neuropathological models. As an instance, investigations on 6-OHDA-induced rat PC12 cells, an in vitro PD model, demonstrated that rutin and isoquercetin have not only a benefic effect on viability and on antioxidant machinery, but also have a direct antioxidant action (Magalingam et al, 2013(Magalingam et al, , 2014(Magalingam et al, , 2016 and modulate several genes to prevent neuronal cell death (Magalingam et al, 2015a). It is noteworthy that rutin has been demonstrated to have more neuroprotective effect with respect to isoquercetin, inducing higher cell viability and better functionality of some antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…2a). On the basis of the data present in literature concerning other quercetin glycosides, a dose of Q3,4'dG 100 Ī¼M was chosen to perform the subsequent experiments (Magalingam et al, 2013(Magalingam et al, , 2015a(Magalingam et al, , 2016.…”
Section: Effect Of Q34'dg On Hsps Proliferation and Viability Duringmentioning
confidence: 99%
“…These findings suggest that quercetin may provide a promising approach for the prevention and treatment of neurodegenerative diseases. Quercetin glycosides rutin and isoquercetin were reported to have neuroprotective effect against 6-OHDA-induced rat pheochromocytoma (PC-12) cells by significantly increasing the activities of catalase, superoxide dismutase, Glutathione peroxidase and glutathione that were reduced by 6-OHDA in PC-12 cells (Magalingam et al, 2016). There was no significant difference in the activation of glutathione peroxidase and glutathione enzymes between rutin and isoquercetin signifying that the two glycosides are equally important in protecting PC-12 cells against 6-OHDA toxicity.…”
Section: Effect On Quercetin On the Nervous System Disordersmentioning
confidence: 99%